The Impact of Human Resources Management Practices as an Entry Point in Crisis Management - lshammari, Wail Shafi; Alhazaimeh, Ahmad Saleh; Alzoubi, Mohammad Omar (Journal of Asian Scientific Research, 2020)
This study aimed to explore the impact of human resources management practices (training, participating in decision-making, motivation, and controlling), trying to build theoretical and practical frame for the effect of human resource practices in fulfilling innovations. And trying to clarify the impact of these practices on crisis management. In addition to introduce suggestions and recommendations to the firms, and to future research in similar topics. The population consisted of the estimated 11 commercial bank employees, operating in Irbid province, out of a total 34 branches, and a randomized judgmental sample were taken from (80) employees working in human resources departments. (71) resolutions deemed fit for analysis recovered. The most important research findings that there is positive statistically significant influence for human resources management practices (training, participating in decision-making, motivation, and controlling)) in crisis management. The study recommends that outsourcing like consultants is another option, consultant that can lead the process.